Red River : Unraveled - Book 6 - Wortham, Reavis Z. (Naperville, IL Poisoned Pen Press, 2016)
Constable Ned Parker has his hands full, between raising his grandchildren, Pepper and Top, and trying to keep the peace in the rural community of Center Springs, Tex. When a car runs off the bridge over Lake Lamar Dam killing Frank Clay, the white mayor, and his black secretary, Maggie Mayfield, local speculation runs rampant. Were they having an affair? Could it have been foul play? If so, who was the target: Frank or Maggie? The incident rekindles an ancient feud between the Clays and the Mayfields, and the body count rises.
Keywords: Police -- Texas; Fiction; Murder -- Investigation; Fiction; Vendetta -- Fiction; Racism -- Texas; Fiction; Texas -- Fiction; Detective and mystery fiction; Historical fiction